Use of wild trout for PBDE assessment in freshwater environments: Review and summary of critical factors - Rios, Juan Manuel; Lana, Nerina Belén; Bertón, Paula; Ciocco, Nestor Fernando; Altamirano, Jorgelina Cecilia (Emerging Contaminants)
Certain wild animals represent sentinels to address issues related to environmental pollution, since they can provide integrative data on both pollutant exposure and biological effects. Despite their technological benefits, PBDEs are considered a threat to environmental health due to their persistence, toxicity, and capacity to be accumulated. These pollutants have been found geographically widespread in fish, particularly in predator species such as trout. The aim of this work is to critically review the applicability and usefulness of wild trout for assessing PBDEs in freshwater environments. Reviewed reports include data from highly industrialized areas as well as areas from remote regions with relatively low human activity, including European and North American great lakes and freshwater environments in Europe, Greenland, subarctic areas and Patagonia, respectively. A summary of relevant factors were grouped into organism-specific factors (food habits, age, size, lipid content, sex and reproduction, tissue type, mechanism of contaminant uptake and metabolism), and PBDE levels in the surrounding environment (sediment). Five wild trout species [rainbow trout (Oncorhynchus mykiss), brown trout (Salmo trutta), lake trout (Salvelinus namaycush), arctic char (Salvelinus alpinus), and brook trout (Salvelinus fontinalis)], collected worldwide within the 1994 to present time frame, were considered. Multivariate techniques (principal component analysis-PCA) and mapping approach, showed clear differences in geographic distribution patterns of PBDE levels in trout depending on the region studied: wild trout from European and North American great lakes have the highest PBDE loads. This pattern could be due to high industrial activity at these locations. A correlational approach used to explore intraspecific relationships between PBDE levels and morphometry, showed positive relationships only for brown trout. Further, brown trout showed the highest trout-to-sediment ratios, which is suggestive of a relatively greater ...